Hematología y química sérica en hembras quelonios (Trachemys scripta callirostris) en la ribera del río Lebrija, Puerto Wilches (Santander) Parte I - Arcila Quiceno, Victor Hernan; Navarro, Richard; Real, Wilson; Rincon, Mauricio; Villamizar, Mauricio (Spei Domus, 2005)
The Trachemys scripta callirostris this classified in the red book (in extinction danger) like a vulnerable species, this is largely due to the inadequate use that has been given to the ecosystem and the irrational and illegal exploitation that the native man of these regions carries out daily, for this reason the interest it arises to look for the form of identifying the techniques of handling of the Tortoises. That it allows to preserve this species. The idea is born of carrying out a study to determine the parameters basic hematologics, and biochemical values (glycemia, uric acid, GPT, GOT, total protein, albumin, triglycerides, cholesterol) like a tool for the diagnosis of different pathologies and like bibliographical reference for the linked personnel of an or another form with the wild fauna. This work was conducted in the Lebrija River, at the municipaly of Puerto Wilches-Santander (Colombia). Was taken 200 turtles – icoteas (Trachemys scripta callirostris), that were distributed in four (4) groups; Its weight ranged from 800 to 2000 grams. 3 ml of blood was collected from each animal (female) by puncture the occipital plexus. Any samples that had obvious hemolysis or clots formation were not used. Plasma biochemical values were determined by use of aspectrophotometric chemistry analyzer. These samples were processed in the laboratory of the Centro Médico Quirúrgico Veterinario of the Universidad Cooperativa de Colombia.